Pengujian Kelayakan Penggantian Current Transformer Di Gardu Induk - Rachmat Sutjipto; Putri Pebrianti; Harrij Mukti K; Rohmanita Duanaputri (Politeknik Negeri Malang, 2026)
At PT PLN (Persero) UIT JBM UPT Gardu Induk Ponorogo, an oil leakage problem was found in the 70 kV (1000/5A, 75VA) S-phase bay coupling CT caused by several factors including: cracks in the tank and damage to the gasket that has lost its elasticity due to age. From the above information, the purpose of this study is to assess the condition of the CT before and after replacement and provide recommendations based on applicable standards. To determine the new CT, the old CT specifications can be used as a reference so that it can improve the operational stability of the new CT both for the measurement process and for protection. From the results of the analysis before the replacement, it shows that the insulation resistance value in 2020 to 2022 has decreased by 52% and the results of the CT thermovision measurement show that the difference in conductor temperature and clamp temperature (Δ) is 36.03°C and does not meet the standards of PLN-SK/DIR/520/2014(0°C-10°C). After the replacement of CT (1000/5A, 40VA) showed an increase in insulation resistance from 67,000 MΩ (2022) to 152,000 MΩ (2023) and the measurement results with thermovision showed a change in ∆? from 36.03°C (2022) to 9.6°C (2023) so that it meets existing standards. These results indicate that CT replacement is a necessary action to maintain CT reliability in the electrical system at PT PLN (Persero) UIT JBM UPT Gardu Induk Ponorogo.